The Effect of Social Support on Adolescent Mental Health: Literatur Review - Harahap, Ana Pujianti; Daramusseng, Andi; Choirunissa, Risza; Nugraheni, Sri Achadi (Jurnal Kedokteran Brawijaya, 2024)
Adolescence is a period that experiences many changes in hormonal, physical, psychological, and social aspects. If not controlled properly, these changes can lead to mental disorders in adolescents. This study aims to explore the relationship between social support and adolescent mental health through literature review. The review analyzed articles sourced from Google Scholar, PubMed, and ScienceDirect as a database with a range of publications between 2012-2022 using the keywords mental health, social support, and adolescents. There were 13 articles that met the inclusion criteria. The result showed that adolescents' mental health is largely determined by the social support surrounding them. Adolescents who lack social support from their families, teachers, and peers will result in bad effects of their mental health. The social support of the nuclear family, especially parents, played a very important role in adolescent mental health. In addition, the factor of the history of adolescents also needed to be considered as a risk factor. Therefore, there is a need for interventions in understanding social support to families, teachers, and adolescents, as well as further research in this topic.